Green marketing and its influence on green consumption, environmental knowledge, brand coolness, and purchase intention of environmentally friendly skincare brands - Rizka Amelia (Indonesian Development of Economics and Administration Journal, 2024)
The development of industrial businesses and the economy has numerous impacts not only on society but also on the environment. The widespread scope of industries and increasing levels of consumption, particularly in the beauty and skincare industry, result in plastic waste that not only pollutes the environment but also contributes significantly to the rise in global temperatures. In response to and to address this issue, many companies are taking steps to contribute to the preservation or at least reduce the adverse environmental impact by initiating eco-friendly product movements. The research employs a quantitative method with a total of 338 respondents from various regions and age groups. The findings of the study indicate that green marketing has a positive influence on increasing brand coolness of a skincare brand and environmental knowledge, green consumption, and overall purchase intention.